Grasping de(centralized) fi(nance) through the lens of economic theory - Jonathan Chiu; Charles M. Kahn; Thorsten V. Koeppl (Bank of Canada, 2022)
In this article, we use a simple stylized model of collateralized lending to analyze the value proposition and limitations of decentralized finance (DeFi). DeFi uses a decentralized ledger to run smart contracts that automatically enforce the terms of a lending contract and safeguard the collateral. DeFi can lower the costs associated with intermediated lending and improve financial inclusion. Limitations are the volatility of the crypto collateral and stablecoins used for settlement, the possible incompleteness of smart contracts and the lack of a reliable oracle. A proper infrastructure reducing such limitations could improve the value of DeFi.
Keywords: G2; 330; Digital currencies and fintech; Payment clearing and settlement systems